Perspectiva estudiantil del papel de las TIC en el aprendizaje de lenguas en pandemia (2025)
This study explores the impact of telepresence education during the COVID-19 pandemic on the development of foreign language competencies, focusing on the challenges and opportunities posed by the integration of Information and Communication Technologies (ICT) in language learning. The research aims to propose strategies to enhance virtual and telepresence learning, based on the perceptions of students from the Modern Languages program at Universidad ECCI. Employing a descriptive, non-experimental design, the study uses structured surveys to assess student perspectives on learning quality, digital skills, academic interaction, autonomous work, and motivation. Results indicate that although students had sufficient digital competencies and managed virtual platforms effectively, they faced significant obstacles such as limited interaction, connectivity issues, and distractions that negatively affected language acquisition. However, they valued interactive activities, familiar content, and autonomous learning approaches, which supported their linguistic development. The study concludes that the effectiveness of telepresence education depends on adequate technological infrastructure and pedagogical strategies tailored to virtual environments.